Statistical Approach for Image Retrieval - Khor, Siak Wang (2007)
Since the emergence of Internet, a gigantic volume of images have been uploaded into the Internet from time to time. Relying on the traditional text-based search approach to locate the required images could no longer meet the diverse needs of users. This persistent trend has demanded a more sophisticated search algorithm on these images.